Risk Factors of Acute Urinary Retention in Benign Prostatic Hyperplasia Patients at Nongkhai Hospital - Nakamont, Tongchai (Health Science Clinical Research, 2020)
Background: Acute urinary retention (AUR) is a most serious complication or long-term disease progression in patients with benign prostatic hyperplasia (BPH). Its effect on patient’s quality of life. Research is needed to predict the risk factors of AUR in clinical practice in Nongkhai Hospital Objective: To determine risk factors associated with acute urinary retention in patients with BPH at Nongkhai hospital Methodology: The data of retrospective case control study were collected from medical records and records in HOSxP program of BPH patients who visited in out-patient urological clinic and emergency room in Nongkhai Hospital from 1 January 2017 –31 December2019. The patients were divided in 2 groups. The study group was men who had acute urinary retention. The control group was men who never had urinary retention during the study period.Demographic data and risk factors were collected . The data was analyzed using univariate analysis and logistic regression analysis at 95% confidence interval. Results: The 693 patients were included to study. The control group were 653 patients and 40 patients were case group. The incident of acute urinary retention rate is 19.24 per 1000 person-year. Age >72 , history of urinary retention, lower urinary tract infection and PSA > 4 are significant associated with AUR by Univariate analysis. But only history of urinary retention, lower urinary tract infection and PSA > 4 are significant associated with AUR by logistic regression analysis. Adjusted odd ratios were 5.565, 3.732 and 3.636 respectively. Consulted: History of urinary retention, lower tract urinary infection and PSA > 4 are risk factors for acute urinary retention in BPH patients. It is useful for predicting acute urinary retention and preparing proper management of BPH patients. Keywords: BPH, acute urinary retention, risk factors